PENGARUH LABA BERSIH DAN ARUS KAS OPERASI DALAM MEMPREDIKSI ARUS KAS OPERASI MASA MENDATANG - Septiana, Amanah; Alamsyah, Sakti; Sulaeman, Sulaeman (Universitas Muhammadiyah Tangerang, 2023)
This study aims to determine the effect of net income and operating cash flow in predicting future operating cash flows. The variables used in this study are net income, operating cash flows, and future operating cash flows. This research was conducted in manufacturing companies in the consumer goods industry sector listed on the Indonesia Stock Exchange (IDX) for the 2017-2019 period as many as 22 companies. The sampling technique in this study used a non-probability sampling method with a purposive sampling technique. Analysis of the data used is non-parametric with multiple linear analysis. With the results of the study, Net Profit has no effect in predicting future operating cash flows with a significance of 0.190 > 0.05 and tcount < ttable (1,338 < 2.037), Operating Cash Flows have a negative effect on predicting future operating cash flows with a significance of 0.000 < 0.05 and tcount > ttable (-3.949 > 2.037), and net income, cash flow has a simultaneous effect in predicting future operating cash flows with a significance of 0.001 < 0.05 Fcount 8.255 > Ftable 3.29. Keyword : Net Profit, Operating Cash Flow, Predicting Future Operating Cash Flows